Training & Development and Performance Management in Organisation: the Malaysian Employees Turnover Intention Study - Koon, Vui Yee; Fung, Han Ping (AeU, 2015)
This study addresses the impact of training and development (TD) and performance management on employee turnover intention in Malaysian Organisations. As TD theoretically influences the turnover intention, the researchers hypothesized that TD would have an indirect effect on turnover intention through performance management. A sample consisting of 633 public and private employees in peninsular Malaysia were involved in this study. Overall, results using structural equation modelling showed that TD has significant effect on turnover intention, and has indirect effect via the mediator. Using multigroup analysis, it was found that the model was invariant within male and female employees. These findings suggest that human resource practices available in organisation that fit with regard to content and process are necessary to improve the behaviour of employees.